Tailoring management practices to the structure of smallholder households in Sudano-Sahelian Burkina Faso: Evidence from current practices. (April 2022) - Berre, David; Adam, Myriam; Koffi, Christophe K.; Vigne, Mathieu; Gautier, Denis
Abstract: CONTEXT: Typologies are widely used to tailor management practices to structural farm households, and to identify recommendation domains. However, it has often been shown that the recommendations are not followed by farmers, especially in the agricultural context of sub-Saharan Africa. OBJECTIVE: We aimed to identify links between a typology based on the structure of farm households and a typology based on farmers' management practices adopted by farmers in the Sudano-Sahelian zone of Burkina Faso. METHODS: We co-developed socio-economic and technical survey with agronomists and socio-economists and collected data on 291 smallholder farming households. We used principal component analysis, followed by hierarchical clustering to build two typologies: a farm household typology and a farm management typology and analyzed the link between the two. RESULTS AND CONCLUSIONS: Our typologies distinguished 4 types of farm households and 3 types of farm management. Although we expected to find a dominant farm management type for each type of farm household, we show that the use of the typology is not sufficient to disentangle the intra-diversity of farm household types, as, except for large-scale cotton producers, of whom 94% fall in the mineral input user category, all the farmers do not use the same set of management practices. For instance, 29.5% of medium-scale cotton-based farm types do not match the "mineral input users" type, but are characterized by their use of mulch and cereal-legume crop rotation. Based on our empirical data, we show that promoting a basket of options (a set of management practices) based on a typology of farm household structure may not always be appropriate. Moving from theory (i.e. use of typology to define 'best fit') to practice (i.e. collecting data on actual agricultural practices), we show that using a combined typology approach will reveal matches and mismatches when practices are tailored to a given farm type. SIGNIFICANCE: In addition to using a farm household typology to tailor practices, we also define a limited set of locally relevant variables that are representative of the diversity of farmers' practices. Graphical abstract: Unlabelled Image Highlights: Typologies are often used to tailor management practices to farm households, but their adoption is limited. Two distinct typologies were built (household and agricultural practices) for 291 farmers in Burkina Faso. Matches and mismatches between farm types and management practices were revealed. Promotion of new agricultural practices only based on farm household structure is not always appropriate. A household typology requires data on real practices to increase the adoption of new agricultural practices.